2017
DOI: 10.1371/journal.ppat.1006702
|View full text |Cite
|
Sign up to set email alerts
|

Estimating virus effective population size and selection without neutral markers

Abstract: By combining high-throughput sequencing (HTS) with experimental evolution, we can observe the within-host dynamics of pathogen variants of biomedical or ecological interest. We studied the evolutionary dynamics of five variants of Potato virus Y (PVY) in 15 doubled-haploid lines of pepper. All plants were inoculated with the same mixture of virus variants and variant frequencies were determined by HTS in eight plants of each pepper line at each of six sampling dates. We developed a method for estimating the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 56 publications
(77 reference statements)
1
43
0
Order By: Relevance
“…However, we detected selection for specific variants of the markers that we used for both the N and S segments during our experiments. We thus adapted a recently developed statistical method (24) to jointly estimate selection coefficients (s) and N e ( Table 1). The results revealed selection in favor of the mys2 over the mys7 marker for segment N and in favor of the mys8 over the mys1 marker for segment S. The statistical analysis also showed that the N e values of the N and S segments of FBNSV were small, varying from Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…However, we detected selection for specific variants of the markers that we used for both the N and S segments during our experiments. We thus adapted a recently developed statistical method (24) to jointly estimate selection coefficients (s) and N e ( Table 1). The results revealed selection in favor of the mys2 over the mys7 marker for segment N and in favor of the mys8 over the mys1 marker for segment S. The statistical analysis also showed that the N e values of the N and S segments of FBNSV were small, varying from Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…These describe features of gene populations, using mathematical models, and compare observed features with those likely to result from sequential random changes. Popgen analyses have been used to study potyvirus populations within plant populations (e.g., Achon [64]; Li et al [65]; Wang et al [66]; Hajizadeh et al [67]) and, increasingly, virus populations within individual plants (e.g., Cuevas et al [68]; Domingo and Perales [69]; Dunham et al [70]; Kutnjak et al [71]; Rousseau et al [72]; Seo et al [73]). Such studies have shown that the effective populations of potyviruses are all around 10,000 [74], and the "The high potential for genetic variation in plant viruses need not necessarily result in high diversity of virus populations.…”
Section: Population Geneticsmentioning
confidence: 99%
“…through the measurement of temporal changes in allele frequencies has remained a major focus of population genetics since the founding of the field (Fisher 1930;Wright 1931). Advancements in sequencing technologies over the last decade have dramatically increased the availability of genomewide time-sampled polymorphism data for a wide variety of organisms, and several methods have been developed to analyze such data (Malaspinas et al 2012;Mathieson and McVean 2013;Foll et al 2014a;Lacerda and Seoighe 2014;Steinrücken et al 2014;Ferrer-Admetlla et al 2016;Schraiber et al 2016;Shim et al 2016;Rousseau et al 2017). Of primary interest is the estimation of site-specific selection coefficients, and new methods account for nonequilibrium demography and environmental fluctuations by, for example, accounting for effective population size, population structure, and changing selection intensities.…”
mentioning
confidence: 99%